Perancangan dan Pembuatan Prototype Sauce Pan dengan Metode Pengecoran - Yahya, Syahril Maula; Suyitno, Suyitno; Hastuti, Sri (Universitas Nusa Cendana, 2024)
Sauce pan or commonly called pan is needed as cooking utensils. There are many sauce pan designs according to the advantages offered by a product. A sauce pan design with a minimal manufacturing process is now required. The purpose of this design is to create a sauce pan design and prototype that can be produced in one casting process between the sauce pan body and the handle connector. The sauce pan was designed using CAD and CAE software to determine the strength of the design. The prototype was made using A356 aluminum. A356 Aluminum as raw material for making sauce pan has many advantages. The strength of the sauce pan is obtained by performing a safety factor simulation with a load of 20 N. The sauce pan design has a good safety factor, with 6.8 for design 1, 4.9 for design 2, and 8.3 for design 3.